2021
DOI: 10.1016/j.cmpb.2021.106113
|View full text |Cite
|
Sign up to set email alerts
|

Data augmentation using generative adversarial neural networks on brain structural connectivity in multiple sclerosis

Abstract: Background and objective: Machine learning frameworks have demonstrated their potentials in dealing with complex data structures, achieving remarkable results in many areas, including brain imaging. However, a large collection of data is needed to train these models. This is particularly challenging in the biomedical domain since, due to acquisition accessibility, costs and pathology related variability, available datasets are limited and usually imbalanced. To overcome this challenge, generative models can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…In medicine, GANs have been used in image synthesis [ 59 ] and radiology applications [ 60 ], or to generate one-dimensional medical signals, such as EEGs [ 61 , 62 ] or ECGs [ 63 ]. Concerning GANs’ applications in diagnosis of MS, papers that can be cited include [ 64 ], in which the number of images is increased to analyze brain structural connectivity, or [ 65 ], in which the authors verify that performing data augmentation on a variety of T1-weighted MRIs improves both tissue and lesion segmentation in MS.…”
Section: Introductionmentioning
confidence: 99%
“…In medicine, GANs have been used in image synthesis [ 59 ] and radiology applications [ 60 ], or to generate one-dimensional medical signals, such as EEGs [ 61 , 62 ] or ECGs [ 63 ]. Concerning GANs’ applications in diagnosis of MS, papers that can be cited include [ 64 ], in which the number of images is increased to analyze brain structural connectivity, or [ 65 ], in which the authors verify that performing data augmentation on a variety of T1-weighted MRIs improves both tissue and lesion segmentation in MS.…”
Section: Introductionmentioning
confidence: 99%
“…Their MCGAN architecture was designed to conditionally optimize the generated nodules’ position, size, and attenuation to enhance the performance of a cascaded 3D CNN-based object detector. Nonetheless, various other contemporary research suggested using GANs to boost the classification performance of different medical imaging modalities, such as works in [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Related Workmentioning
confidence: 99%
“…These studies are examples of how the analysis of big data by ML approaches offers considerable advantages, such as flexibility, scalability and the ability to analyze diverse data, compared with traditional biostatistical methods. Furthermore, in one study several ML models were combined (“ensemble learning”), proving to be more performant than single models to estimate disability in MS ( Barile et al, 2021a ).…”
Section: Clinical Applications Of Aimentioning
confidence: 99%